Performance Evaluation of Some Manually Operated Weeders Used in Jhum Cultivation in Hill Regions of Arunachal Pradesh - Singh, M. U. (Indian Journal of Hill Farming, 2018)
weeding is a labour intensive and time consuming operation in Jhum cultivationsystem inÂ hill region of Arunachal Pradesh. However the scarcity of labour during the peak season results in increased of labour wages and delay in weeding operation which ultimatelyreduced the yield of crop. The present study was undertaken with an objective to evaluatefield performance of four different types of manually operated weeders namely push pullweeder with five tines, push pull weeder with sweep blade, peg type dry-land weeder and straight blade hand hoe. The trail was conducted in the farmerâ€™s cabbage field located at Lakhi village of Papum Pare district of Arunachal Pradesh. The average effective field capacity of 0.0185, 0.022, 0.016, and 0.017 ha/h, respectively were observed for wheel hoe with five tine, wheel hoe with sweep blade, peg type dry-land weeder and straight blade hand hoe at forward speed of 0.285, 0.338, 0.290 and 0.270 m/s respectively. The result revealed that maximum weeding efficiency of 79.72% was recorded for sweep type followed by straight blade (78.19%), tine type (75.71%) and peg type dry-land weerder (72.50%). Push pull weeder with sweep type blade also recorded the lowest labour requirement of 51 man-h per hectare followed by 56 man-h, 66 man-h and 70 man-h per hectare for push pull five tines weeder, straight blade hand hoe and peg type dry-land weeders respectively. Percentage plant damage was highest under straight blade hoe (2.5%) followed by push pull with five tine (1.5%), push pull with sweep blade (1%) and peg type dry-land weeder (0%).Among the weeders, peg type dry-land weeder required minimum power input of 0.071 kW (0.096 hp) followed by straight blade hoe 0.079 kW (0.107 hp), push pull with sweep blade 0.105 kW (0.142 hp) and push pull with five tine weeder 0.112kW (0.152 hp). However themaximum performance index of (1222.75) was observed for push pull weeder with sweepblade followed by straight blade hand hoe (121 1.21), peg type dry-land weeder (1208.33)and push pull weeder with five tines (976.34).